2006
DOI: 10.1007/s10826-006-9048-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychological functioning in siblings of children with Attention Deficit Hyperactivity Disorder

Abstract: We examined psychological functioning in siblings of children with Attention Deficit Hyperactivity Disorder (ADHD). Siblings of children diagnosed with ADHD (n = 45) between the ages of 9 and 13 and a control group (n = 46) within the same age range composed of siblings of children with no diagnosed disorders completed measures of psychological functioning. A significant multivariate difference was observed on these measures across groups. Post hoc investigation of the univariate means revealed one significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Researchers presenting this attitude continue to maintain negative presuppositions about the influence of a child with a disability on the family, despite new shifts in modern psychology. In accordance with new trends, a growing number of researchers have conducted studies to look for optimistic results related to these unique sibling relationships, such as an optimal level of assertiveness, empathy and resilience (Bellin, Bentley, & Sawin, 2009;Jones, Welsh, Glassmire, & Tavegia, 2006). Siblings of disabled children were characterized by maturity, responsibility and protection (Bellin & Rice, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers presenting this attitude continue to maintain negative presuppositions about the influence of a child with a disability on the family, despite new shifts in modern psychology. In accordance with new trends, a growing number of researchers have conducted studies to look for optimistic results related to these unique sibling relationships, such as an optimal level of assertiveness, empathy and resilience (Bellin, Bentley, & Sawin, 2009;Jones, Welsh, Glassmire, & Tavegia, 2006). Siblings of disabled children were characterized by maturity, responsibility and protection (Bellin & Rice, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear whether siblings in this study had these feelings but they were not manifested in feelings of depression or anxiety, or whether the siblings simply did not have these feelings of resentment, victimization, minimization, and frustration. However, given the findings by Jones et al (2006) of significant self-reported feelings of anger, yet no significant findings for self-reported feelings of anxiety or depression, it may be that although siblings do experience some concerns (i.e., anger, resentment, victimization), they do not internalize these symptoms in terms of feelings of depression or anxiety.…”
Section: Discussionmentioning
confidence: 85%
“…The current study expanded on the previous literature by using quantitative child self-report measures of depression and anxiety to further explore child internalizing symptoms, which only scant research had previously examined. Furthermore, this study addressed some of the limitations of the study by Jones et al (2006) by providing a standardized administration of the self-report measures by trained investigators and assessing for symptom severity in the child diagnosed with ADHD. It had been anticipated that the previous reports of siblings' feelings of resentment, victimization, minimization, and frustration (Kendall, 1999;Singer, 1997), based on interviews with siblings of children diagnosed with ADHD, would be reflected in self-reports of more internalizing problems as assessed by the CDI and the MASC; however, this was not found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 In our study, there were few differences between unaffected siblings and healthy school control subjects, indicating that unaffected siblings are more like their typically developing counterparts. 47 However, further follow-up of unaffected siblings is needed to determine whether a yet unexpressed vulnerability to psychopathology will emerge in their transition from adolescence into adulthood. 18 The only exception was that unaffected siblings had an increased risk of ever use of alcohol.…”
Section: Psychiatric Comorbidities In Unaffected Siblingsmentioning
confidence: 99%